A internacionalização na educação profissional e tecnológica: um estudo de caso do Projeto Lapassion - Chagas, Emanuelle Lorena Teixeira (2021)
The present study aims to investigate w hether internationalization actions within the scope of professional and te chnological education (EP T) can effectively contribute to the development of the integral huma n formation of its stu dents, as a basis for a proposal for a professional formati on cou rse. The process of internationalization in education consists of a series of actions that range fro m encouraging student exchanges to teaching languages. Thus, the inte ntion was to analyze t he concept of integral human formation in the context of E P T ; to know the phenomenon of the internationalization of education and how it has been happening within th e IFAM, from the perspective of the participants of an international exchange project and, finally, to develop a proposal for professional training ai med at training interested teachers, technicians and managers in planning, organi zing and executing an int ernational multidisciplinary, multilevel, multicultural and multi lan guage project in their own educational insti tution. This qualitative and quantita tive r esearch used the case study method in which the investigation focused on th e Lapassion project, whic h was an exchange program that took place at the Manaus Industrial Di strict Campus of IFAM, from March 2020 to Ma y of the same. year, whose objective was th e development of social emotional and interpersonal skills, using a tool fo r solving problems and cr eating innovative products and services known as Design Thinking. At the end of the project , the students volunta rily answered an evaluation questionn aire a nd a semi structured interview. From these two instruments, data were obtai ned and analyzed in the l ight of Textual Discursive Analysis (GALIAZZI; MORAES, 2016), which i ndicate that the proje ct significantly contr ibuted to the development of skills s uch as leadership, conflict management, creativity , teamwork, among other skills known in the literature as soft skills, in addition to having effectively collaborated for th e professional trainin g of participating stu dents, highlighting the expansion of their intercultural relations, the improvement in communication in a foreign lang uage, the promotion of a education with a scientific bias, socio affective development and the civic education for t hose students. The res earch resulted in the educational pro duct: Design Thinking Course for the development of innovative products and servi ces at an international l evel, encompassing the concepts of the method, its steps, approach st rategies, a Lapassion video showing the meth odology in practice, tips and example s for deepening of the themes, in addition to general guidelines for the preparat ion of the course, rangin g from the choice of the location to the official language of the pro ject. The product, upo n evaluation of profes sionals who participated as professor s, org anizers or collaborators of Lapassion, received a favorable evaluation in i ts objective to train emp loyees of educational institutions for the development of internation al projects